An unprecedented dioxygen species revealed by serial femtosecond rotation crystallography in copper nitrite reductase. (2018) - Halsted, Thomas P.; Yamashita, Keitaro; Hirata, Kunio; Ago, Hideo; Ueno, Go; Tosha, Takehiko
No abstract available